Semantic‐based representation, enrichment and computation of product breakdown structures. (28th October 2015) - Alvarez‐Rodríguez, Jose María; Llorens, Juan; Alejandres, Manuela; Fuentes, Jose Miguel
Abstract: Product breakdown structures (PBS) are considered a cornerstone in the development of safety critical systems. In this context, the dramatic increase of the amount of applications, management platforms or services imply a tangled environment of data formats, models or protocols that prevent a proper re‐use of data and information resources. Recent times have seen the development of the Open Services for Lifecycle Collaboration (OSLC) initiative to exchange domain‐based knowledge under a common and shared data model (RDF) and to access services under web‐based protocols. The present paper introduces a method and a model to represent a PBS applying a profile‐based approach using RDF‐based vocabularies. Moreover, a hybrid method to validate data, information and structure of a PBS is also introduced. Finally, a case study is conducted to compare traditional PBS management methods to a Linked Data based PBS using the Analytical Hierarchy Process (AHP) and the Service Measurement Index (SMI).